Health-related quality of life and mental health of children with embryonal abdominal tumors - Behrendt, Paulina; Boettcher, Michael; Zierke, Kira Tabea; Najem, Safiullah; Zapf, Holger; Reinshagen, Konrad; Wößmann, Wilhelm; Boettcher, Johannes (Children, 2023)
(1) Background: Embryonal abdominal tumors are one of the most common entities of solid childhood cancer. The present study investigates the Health-Related Quality of Life (HRQoL) and the mental health of children to obtain a comprehensive picture of their health status and uncover a possible gap in healthcare. (2) Methods: The sample consisted of 54 children who were treated for embryonal abdominal tumors and a control group of 46 children who received uncomplicated outpatient surgery. The HRQoL and the mental health were assessed by the parent proxy reports of the questionnaires Pediatric Quality of Life Inventory (PedsQL) and Strengths and Difficulties Questionnaire (SDQ). (3) Results: Children with embryonal abdominal tumors showed significantly lower HRQoL and mental health values compared to the norm data. The index group showed lower values in the social subscales of HRQoL and mental health compared to the control group. (4) Conclusions: Embryonal abdominal tumors affect the well-being of children. There is still a gap in healthcare due to children’s HRQoL and mental health, especially regarding social development. It is essential to further advance the psychological care of children and improve their chances to develop social relationships.